IDENTIFICATION AND PREDICTION OF COASTLINE CHANGES IN BANYUWANGI REGENCY DUE TO CLIMATE CHANGE USING GRASS QGIS - Erwanto, Zulis; Holik, Abdul; Sanjaya, Aditya Wiralatief (ASTONJADRO, 2021)
Banyuwangi Regency has a coastline of 175.8 kilometers, stretching from Meru Betiri National Park to Baluran National Park. Coastline changes occur due to human activities, abrasion and sedimentation due to climate change and global warming. Research to identify and predict changes in the coastline of Banyuwangi Regency due to climate change using GRASS QGIS in 2025. The results of predictions of shoreline changes in Banyuwangi Regency are located in Pang Pang Bay, Muncar District and Tegaldelimo District. In Banyuwangi Sub-district on Cacalan Beach, Cemara Beach and Marina Boom Beach, and on the southern coast of Banyuwangi in Purwoharjo District, namely Grajagan Beach, and in Pesanggaran District on Red Island Beach. Recommendations for mitigating shoreline changes with sandy and swampy beach types in addition to the application of ecotourism principles are also the implementation of wind barriers, mangrove rehabilitation, seawall construction, or TetraPOT. Vegetative and mechanical conservation efforts are a strong combination in natural and artificial defense from marine abrasion attacks.